Polish Independent Press Summary, no. 14 (1988) - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
A digest of Polish underground press (including articles, tables of content, and book covers) compiled by members of the RFE Polish Underground Publications Unit to be used in a daily 20-minute broadcast on Polish samizdat. Extract from Tygodnik Mazowsze, no. 232 (16 December 1987). Extract from Przegląd Wiadmości Agencyjnych, no. 44 (16 December 1987). Extract from Przegląd Wiadmości Agencyjnych, no. 45 (23 November 1987). Extract from Region, no. 2 (6 December 1987). Extract from Solidarność Opolska, no. 27 (November 1987). Extract from Paragraf, no. 29 (21 November 1987). Extract from CDN - Głos Wolnego Robotnika, no. 216 (2 December 1987). Extract from Solidarność Podbeskidzia, no. 93 (16 November 1987). Extract from Horyzont, no. 5 (6 December 1987). Table of Contents from Prawo i Bezprawie, no. 7 (June 1987). Extract from Prawo i Bezprawie, no. 7 (June 1987). Table of Contents from Spotkania, no. 33/34 (1987). Extract from Spotkania, no. 33/34 (1987). Table of Contents from Kultura Niezależna, no. 34 (October 1987). Extract from Kultura Niezależna, no. 34 (October 1987).